Effects of boron toxicity on growth, oxidative damage, antioxidant enzymes and essential oil fingerprinting in Mentha arvensis and Cymbopogon flexuosus - Sadaf Choudhary; Andleeb Zehra; M. Naeem; M. Masroor A. Khan; Tariq Aftab (Chemical and Biological Technologies in Agriculture, 2020)
Abstract Background Boron (B) is an essential micronutrient and necessary to plants for their proper growth. The concentration of B in soil and plant is greatly critical for the growth and productivity. Even at the low amount available in soils, B can be extremely toxic to plants especially in semi-arid and arid environments. In the present study, the effects of high B concentrations (2.5, 5, 10, 20 and 30 mg/kg) were elucidated on two important essential oil-bearing plants; Mentha arvensis and Cymbopogon flexuosus which are aromatic and antimicrobial herbs having well-known medicinal values. Results Application of different concentrations of B showed growth inhibitory effects on plant as evident by shoot and root lengths, fresh and dry weights of shoot in the studied plants. Treatments of B also reduced the total chlorophyll and carotenoid content, chlorophyll fluorescence and reduced the activities of carbonic anhydrase and nitrate reductase enzymes. Moreover, B stress considerably increased the proline content and lipid peroxide content as compared to control. The activities of antioxidant enzymes like catalase, peroxidase and superoxide dismutase were also significantly increased under B stress. The content of essential oil of M. arvensis and C. flexuosus increased at 2.5 mg/kg of B and decreased with further increase in concentrations of B. Conclusion The findings of present work suggest that increasing concentrations of B inhibited growth and photosynthetic pigments, increased oxidative damage and activities of antioxidant enzymes; however, a mild stress of B increased essential oil production in M. arvensis and C. flexuosus plants.